Depression and anxiety of medical students at Kunming Medical University during COVID-19: A cross-sectional survey - Guo, Ying; Li, Shunda; Zhang, Lanchun; Xuan, Qun; He, Liu; Ye, Qingyan; Ma, Jiaqing; Peng, Li; Xiong, Yunxia; Yang, Jianyu; Yu, Haofei; Xie, Jianping; et al. (Frontiers in Public Health, 2022)
The COVID-19 pandemic is detrimental to people's mental health. The purpose of this study was to investigate the prevalence of and risk factors for depression and anxiety among medical students and to provide ideas for the prevention of depression and anxiety among medical students. A cross-sectional survey was conducted among 2,116 medical students at Kunming Medical University from July 8 to July 16, 2020. Participants’ demographic and living conditions were collected. Depression and anxiety were measured using the Patient Health Questionnaire 9 and General Anxiety Disorder-7 (GAD-7), respectively. Uni- and multivariate logistic regression analyses were performed to detect risk factors associated with depression and anxiety. The prevalence rates of depression and anxiety among medical students were 52.5% and 29.6%, respectively. Medical students who were in their first year (freshmen) and second year (sophomores), exercised once per week, took medicine once per week, ate abnormally more than or equal to once per week, spent more than 2 hours per day on the smartphone, were concerned about the impact of COVID-19, considered offline teaching almost inadaptable, and were anxious had a higher risk of depression. Students who took medicine more than twice per week, ate abnormally more than twice per week, considered offline teaching inadaptable, and were depressive were more likely to have anxiety symptoms. Students who exercised once or twice per week had a lower risk of anxiety. Our study identified a major mental health burden on medical students during the COVID-19 outbreak. More targeted measures should be taken to improve the mental state of students to reduce the incidence of depression and anxiety.